Beyond the body image: A qualitative study on how adults experience lower limb amputation - Senra, Hugo Renato Carreira Gomes (2012)
Objective: To explore adults’ experiences of lower limb amputation, focusing on the changes in self-identity related to the impairment. Design: A cross-sectional and qualitative study, using semi-structured interviews. Interviews were transcribed, coded and analysed by two independent researchers. Setting: A rehabilitation medicine service from a general public hospital. Participants: A convenience sample of 42 patients with lower limb amputation performed after the age of 18 and followed up in the physical medicine and rehabilitation department of a general hospital. Main outcome measures: A semi-structured interview, addressing three core areas: the emotional impact of amputation; the adjustment process; and the relation with the external resources. Results: Eight themes emerged from interviews: reactions and feelings about becoming amputee; changes in own life; problems in well-being; relation with the prosthesis; self-perceptions; aims related to the rehabilitation and future plans; relation with the rehabilitation; and perceived social support. These results supported a theoretical model for the self-identity changes related to limb loss. Conclusions: The self-identity changes after a lower limb amputation appear beyond the patient’s body image and functioning, affecting the patient’s awareness of the impairment, biographical self and any future projections.